STRATEGIC RESPONSE TO INTERNATIONAL STANDARDS: INSIGHTS FROM THE BRAZILIAN BEEF CHAIN - Marques Vieira, Luciana (Revista Eletrônica de Administração, 2013)
While Globalisation in the agri-food sector may provide opportunities for companies in developing countries to access international markets, it also threatens the existence of some sub-sectors. This paper reviews existing literature on co-ordination and international standards, identifying the importance of both to supply chain management. In the context of the Brazilian beef export chain, this paper contributes to the question of how exporters are changing their transaction practices in order to respond efficiently to those standards. In-depth interviews with key people and summaries of case study findings highlight the impact of international standards on the organisation of the export supply chain. It is highlighted that to be globally competitive, traditional mistrust and opportunism need to be overcome by the formation of network or quasi integration strategies between processors and suppliers. Prediction shows that sharing market information would lead to a supply chain management and could be considered trading-up.